Antimetastatic effects of Citrus-derived bioactive ingredients: Mechanistic insights - Farooqi, Ammad Ahmad; Tahir, Fatima; Fakhar, Maham; Butt, Ghazala; Colombo Pimentel, Tatiana; Wu, Ning; Yulaevna, Ishmuratova Margarita; Attar, Rukset (Cellular and Molecular Biology, 2021)
The growing complexity of metastasis has sparked tremendous interest in unraveling of the underlying mechanisms which play fundamental role in cancer progression and metastasis. Ground-breaking discoveries in metastasis research have greatly enhanced our understanding about intricate nature of metastasis. Bioactive chemicals obtained from citrus fruits have gained noteworthy appreciation because of significant cancer chemopreventive roles. Deregulated oncogenic signaling cascades play central role in metastasis. Emerging evidence has started to shed light on the metastasis inhibitory properties of naringin, naringenin, tangeretin, nobiletin, hesperidin and hesperetin in different cancer cell lines and xenografted mice. Wnt/β-catenin, TGF/SMAD and NOTCH signaling cascades have been shown to play linchpin role in carcinogenesis and metastasis. There is emerging evidence related to pharmacological targeting of Wnt/β-catenin, TGF/SMAD and NOTCH by citrus-derived bioactive components. These findings are indeed encouraging and will enable researchers to gain further insights into pharmacological targeting of oncogenic pathways to inhibit and prevent metastasis.